Prophets and witches - Parish, Debra, author.
1 online resource
Keywords: Prophets and Witches offers an exploration of female prophecy and witchcraft during the political and religious upheavals of the English Revolutionary period from 1640 to 1660.The religious fervour and End of Days enthusiasm precipitated by the Civil War opened the door for unprecedented numbers of women to achieve visibility and spiritual authority as prophets. However, as self-proclaimed instruments for God's spirit, these women were also exposed to the charge of demonic possession or witchcraft. This book explores both the gender and political elements at work in the construction of the prophet as a witch. It uncovers the role of witchcraft in the dominant political and religious debates and power conflicts of the times, which provides a crucial framework for the female prophet's transformation from divine instrument to demonic witch. This study of the early modern prophet and witch reveals the fluidity, and at times close relationship of these assumed opposites.This book is a valuable resource to students and scholars of early modern England, the English Civil War and all readers interested in female religiosity, prophecy, witchcraft, demonology and early Quakerism.